Study on Electrophysiological Signal Monitoring of Plant under Stress Based on Integrated Op-Amps and Patch Electrode. (10th October 2017) - Cai, Weiming; Qi, Qingke
Abstract : Electrophysiological signal in plant is a weak electrical signal, which can fluctuate with the change of environment. An amplification detection system was designed for plant electrical signal acquisition by using integrated op-amps (CA3140, AD620, and INA118), patch electrode, data acquisition card (NI USB-6008), computer, and shielded box. Plant electrical signals were also studied under pressure and flooding stress. The amplification detection system can make nondestructive acquisition for Aquatic Scindapsus and Guaibcn with high precision, high sensitivity, low power consumption, high common mode rejection ratio, and working frequency bandwidth. Stress experiments were conducted through the system; results show that electrical signals were produced in the leaf of Aquatic Scindapsus under the stress of pressure. Electrical signals in the up-leaf surface of Aquatic Scindapsus were stronger than the down-leaf surface. Electrical signals produced in the leaf of Guaibcn were getting stronger when suffering flooding stress. The more the flooding stress was severe, the faster the electrical signal changed, the longer the time required for returning to a stable state was, and the greater the electrical signal got at the stable state was.